THE EFFECT OF THE IMPLEMENTATION OF GOOD CORPORATE GOVERNANCE ON THE COMPANY FINANCIAL PERFORMANCE - Aminah AMINAH; Nurdiawansyah Nurdiawansyah (UBL, 2016)
This study aims to test and analyze the effect of implementation Good Corporate Governance on the company financial performance. The population in this study is all of the companies which registered as CGPI’s canidate of 3 years period (2012-2014) and listed in Indonesian Stock Exchange. Sampling using purposive sampling in order a total sample of 11 companies that meet the criteria of the study sample set. The results showed that implementation of GCG that respresented by scoring CGPI, and measurement of the company financial performance is based on profitability ratios which is ROA, ROE, and NPM. The results showed that implementation of GCG that respresented by scoring CGPI negatively affect and insignificant on ROA. While the implementation GCG has positive effect but insignificant on ROE. On the other hand, the implementation of GCG has positive effect and significant on the performance of financial company that measured by NPM. It means that implementation of GCG don’t give a significant effect on the company financial performance.